2022
DOI: 10.3389/fphar.2022.799064
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin as a Major Bioactive Compound in the Vasorelaxant Effect of Different Pigmented Rice Bran Extracts

Abstract: Cardiovascular disease is one of the leading causes of morbidity and mortality in recent years. The intake of polyphenol rich diets has been associated with improved cardiovascular function and reduced cardiovascular risks. Oryza sativa L. is one of the most common cereals worldwide. Rice bran, a byproduct of the rice milling process, contains many bioactive ingredients, including polyphenols, polysaccharides, proteins, and micronutrients. It is also consumed as a healthy diet in the form of rice bran oil and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…Like previous findings, TFN treatment mitigated the Cd-induced increase in G6P levels markedly . Taxifolin’s robust antioxidant and anti-inflammatory potential has been established in the literature. Similarly, in the current experimental design, TFN reduced oxidative stress induced by CdCl 2 through the modulation of first-line antioxidant enzymes and decreased inflammation by modulating key inflammatory cytokines IL-6 and TNF-α. , CdCl 2 is an obesogenic factor, as its administration led to increased levels of fatty acids, cholesterol, TGs, and FFAs, consistent with the literature . However, treatment with TEE mitigated hyperlipidemia by modulating hepatic lipoprotein synthesis and other multiple lipid-lowering pathways .…”
Section: Discussionsupporting
confidence: 87%
“…Like previous findings, TFN treatment mitigated the Cd-induced increase in G6P levels markedly . Taxifolin’s robust antioxidant and anti-inflammatory potential has been established in the literature. Similarly, in the current experimental design, TFN reduced oxidative stress induced by CdCl 2 through the modulation of first-line antioxidant enzymes and decreased inflammation by modulating key inflammatory cytokines IL-6 and TNF-α. , CdCl 2 is an obesogenic factor, as its administration led to increased levels of fatty acids, cholesterol, TGs, and FFAs, consistent with the literature . However, treatment with TEE mitigated hyperlipidemia by modulating hepatic lipoprotein synthesis and other multiple lipid-lowering pathways .…”
Section: Discussionsupporting
confidence: 87%
“…S. fruticosa species was the only one with quantifiable amounts of this compound. This compound was recently associated with positive effects in nitric oxide production and endothelial dysfunction, contributing to a vasorelaxant effect and cardiovascular protection [ 90 ]. Compounds 28 , 57 , and 79 , not classified in the previous classes, were less abundant in the plants and present in D. crassifolium , I. crithmoides, and M. nodiflorum, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that NOS activity increased four-fold after TAX administration, which indicated elevated NO bioavailability followed by increased endothelium-dependent relaxation. A study in which TAX was included in a red rice extract showed that TAX was the major active substance that exhibited strong endothelium-dependent vasorelaxant properties that were, at least, partially mediated via NO-dependent signaling through the phosphoinositide 3-kinase/eNOS pathway [ 26 ]. However, in our study, the elevation of NOS activity was not associated with elevated eNOS protein expression but with elevated iNOS protein expression without any change in the corresponding Nos genes, suggesting a TAX effect upon translation and/or activation of individual NOS isoenzymes.…”
Section: Discussionmentioning
confidence: 99%